Positive roadside edge effects on artificial nest survival in a lowland Atlantic Forest. Issue 13 (14th June 2019) - da Silva, Gleidson Ramos; Diniz, Pedro; Banhos, Aureo; Duca, Charles
Abstract: Road construction is considered to be one of the primary causes of forest fragmentation, and little is known about how roads affect bird reproductive success. The objective of this study was to assess the survival rate of artificial nests along an edge associated with a highway and in the interior of a tabuleiro forest. The study was performed at the Sooretama Biological Reserve, on the margins of federal highway BR‐101, between September and October 2015. A total of 168 artificial nests with a Common quail ( Coturnix coturnix ) egg in each nest were placed along six sampling transects, at distances of 2, 25, 50, 100, 200, 400, and 800 m from the highway toward the forest interior. We used logistic regression and estimated daily survival rate (DSR) using the "Nest Survival" function in the program MARK to estimate artificial nest survival and assessed the effect of the distance from the highway. The artificial nest survival rate was significantly higher on the highway margins than at other distances. The results show that artificial nests located up to 25 m from the highway have a greater success probability (over 95%) and a significant decrease in success probability more than 50 m from the highway. Although we cannot rule out other nonroad‐specific edge effects on artificial nest predation, our results suggest that the impacts of the highway (e.g., noise, vibration, visual stimuli) cause predators to avoid the road's surroundings (up to 25 m into the forest) when selecting their feeding sites, which partially supports the predation release hypothesis. Abstract : This study was to assess the survival rate of artificial nests along an edge associated with a highway and in the interior of a Tabuleiro forest. Our results suggest that the impacts of the highway cause predators to avoid the road's surroundings, which partially supports the predation release hypothesis.